Distribution and impacts of long-lasting marine heat waves on phytoplankton biomass - Chauhan, Anshul; Smith, Philip A. H.; Rodrigues, Filipe; Christensen, Asbjørn; St. John, Michael; Mariani, Patrizio (Frontiers in Marine Science, 2023)
Warm temperature anomalies are increasing in frequency in the global ocean with potential consequences on the goods and services provided by marine ecosystems. Recent studies have analyzed the distribution and dynamics of marine heat waves (MHWs) and evaluated their impacts on marine habitats. Different drivers can generate those anomalies and the emerging attributes can vary significantly both in space and time, with potentially different effects on marine biology. In this paper we classify MHWs based ontheir attributes and using different baselines, to account for different adaptive responses in phytoplankton dynamics. Specifically, we evaluate the impacts of the most extreme, long-lasting and high-intensity MHWs on phytoplankton communities using remote sensing data. We demonstrate marginal impacts on total chlorophyll concentrations which can be different across different ocean regions. These contrasting effects on phytoplankton dynamics are most likely the results of the different mechanisms generating the MHWs in the first place, including changes in front dynamics, shallower mixed layers, and eddy dynamics. We conclude that those drivers producing extreme MHWs can also induce different phytoplankton responses across the global ocean.